Analysis of Sports Injuries among High School Athletes in 18 West Central Florida Schools - Karen D. Liller; Siew Wong-Jacobson; Barbara Morris; Yingwei Yang (University of North Florida, 2016)
Through this study we report the 2014-15 injuries of high school athletes in 18 west central Florida schools utilizing the Reporting Information Online (RIO) data system. Certified athletic trainers (ATCs) were hired and trained by researchers from the University of South Florida to collect and report injury findings from high school athletes. Descriptive statistics, injury rates, and rate ratios were calculated. Overall, 726 injuries were reported by the ATCs. Football was the leading sport for number of injuries and injuries per athlete-exposures for practices and competitions. Boys had significantly greater injury rates compared to girls overall and in competitions and practices. Our results show the important role football continues to play in high school sports injuries and help lay the groundwork for the development of targeted interventions for athletes.